2013
DOI: 10.1002/path.4129
|View full text |Cite
|
Sign up to set email alerts
|

The splicing factor SRSF6 is amplified and is an oncoprotein in lung and colon cancers

Abstract: An increasing body of evidence connects alterations in the process of alternative splicing with cancer development and progression. However, a direct role of splicing factors as drivers of cancer development is mostly unknown. We analysed the gene copy number of several splicing factors in colon and lung tumours, and found that the gene encoding for the splicing factor SRSF6 is amplified and over-expressed in these cancers. Moreover, over-expression of SRSF6 in immortal lung epithelial cells enhanced prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
123
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 54 publications
4
123
1
Order By: Relevance
“…The SRSF6 gene encodes a protein that is involved in mRNA splicing and its overexpression is suggested to contribute to the development of lung and colon cancers. 20 C. pneumoniae seropositivity may be a risk factor for lung cancer, with higher anti-C. pneumoniae antibody titer correlated with cancer risk. 21 Although the mechanism by which infection with C. pneumoniae may increase the risk of lung cancer is not known, one possible explanation is that it may induce irregular apoptosis in tissues.…”
Section: Discussionmentioning
confidence: 98%
“…The SRSF6 gene encodes a protein that is involved in mRNA splicing and its overexpression is suggested to contribute to the development of lung and colon cancers. 20 C. pneumoniae seropositivity may be a risk factor for lung cancer, with higher anti-C. pneumoniae antibody titer correlated with cancer risk. 21 Although the mechanism by which infection with C. pneumoniae may increase the risk of lung cancer is not known, one possible explanation is that it may induce irregular apoptosis in tissues.…”
Section: Discussionmentioning
confidence: 98%
“…For example, alterations in alterative splicing of the APC, K-Ras and TP53 genes have been implicated in the context of multiple carcinogenesis of CRC 15 . In addition, upregulation of typical SR proteins such as SRSF1 and SRSF6 was previously observed in colon cancers, although misregulated splicing events by them have not been identified 33,34 . These findings suggested that genetic lesions or dysregulation of splicing factors that affect alternative splicing are likely to contribute significantly to the aetiology of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that alternative splicing factors play a major role in cancer development and progression (Karni et al 2007;Golan-Gerstl et al 2011;Quesada et al 2012;Cohen-Eliav et al 2013). Moreover, genomewide deep sequencing studies conducted recently on several types of cancer or premalignant diseases discovered mutations in splicing factors and suggest that these mutations are driver mutations (Papaemmanuil et al 2011;Imielinski et al 2012;Quesada et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mutations in several components of the spliceosome were recently discovered in several cancers and are predicted to be driver mutations, providing further confirmation that splicing factors are indeed important players in cancer development (Papaemmanuil et al 2011;Quesada et al 2012). However, there is only limited information regarding the causal/functional role of alternative splicing regulators in cancer development and progression (Karni et al 2007;Jia et al 2010;Golan-Gerstl et al 2011;Lefave et al 2011;Anczukow et al 2012;Cohen-Eliav et al 2013).…”
Section: Introductionmentioning
confidence: 99%